If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + 7) = 3(x + -1) Reorder the terms: 4(7 + 2x) = 3(x + -1) (7 * 4 + 2x * 4) = 3(x + -1) (28 + 8x) = 3(x + -1) Reorder the terms: 28 + 8x = 3(-1 + x) 28 + 8x = (-1 * 3 + x * 3) 28 + 8x = (-3 + 3x) Solving 28 + 8x = -3 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 28 + 8x + -3x = -3 + 3x + -3x Combine like terms: 8x + -3x = 5x 28 + 5x = -3 + 3x + -3x Combine like terms: 3x + -3x = 0 28 + 5x = -3 + 0 28 + 5x = -3 Add '-28' to each side of the equation. 28 + -28 + 5x = -3 + -28 Combine like terms: 28 + -28 = 0 0 + 5x = -3 + -28 5x = -3 + -28 Combine like terms: -3 + -28 = -31 5x = -31 Divide each side by '5'. x = -6.2 Simplifying x = -6.2
| -8x+2x-6=-5x+7x | | w+2/3=3 | | 4x^2=178 | | 5-2x+6=1 | | ln(y-4)-ln(9)=x+ln(x) | | 6(3x+1)=7(2x-3) | | -3x(x-6)=18 | | 3(-2)+4[14-4]= | | y*y=5*5+(5*3)*(5*3) | | 2m-10=4-2(m-5)-12 | | (6x-41)2=180 | | 6x-41=180 | | 11(3x-2)=5(6x-5) | | (6x+-41)*2+(3x+22)2=360 | | -56+8= | | 4(3y-7)-(13y-2)= | | (6x-41)2+(3x+22)=360 | | -3x(x-6)=6 | | (6x-41)2+(3x+22)2=360 | | xy+15x=(y+15) | | 16y^2+48y=0 | | -7+-33n= | | z-(2z-[3z-(4z-5z)-6z]-7z)-8z= | | -35n+2n= | | 8-2(3m-7)=-5m+11m+3 | | 35n+2n= | | x^4-7x-44=0 | | 2x+3=87 | | 6-4x+8x=12 | | 6y-7=32 | | 16y^2+48y+72=0 | | 2b+5=8b+1 |